2019
DOI: 10.1088/1674-1056/28/4/048703
|View full text |Cite
|
Sign up to set email alerts
|

Effect of terahertz pulse on gene expression in human eye cells

Abstract: In recent years, the advances in terahertz applications have stimulated interest in the biological effects associated with this frequency range. We study the gene expression profile in three types of cells exposed to terahertz radiation, i.e., human ARPE-19 retinal pigment epithelial cells, simian virus 40-transformed human corneal epithelial cells, and human MIO-M1 Müller cells. We find that the gene expression in response to heat shock is unaffected, indicating that the minimum temperature increases under co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…These researchers found that terahertz waves promoted the differentiation of mouse pluripotent stem cells after 12 h of radiation by upregulating the expression of peroxisome proliferator-activated receptor gamma, adiponectin, glucose transporter 4 and human adipocyte fatty acids. Zhao et al [58] used a wide-band terahertz source to radiate three different types of cells, epithelial cells, human corneal epithelial cells and human M lymphocytes, under an 800 nm pulse with a repetition rate of 1 kHz, an average power of 1 mW and a peak power of up to 2 mW. Six hours after radiation, the expression of numerous genes, such as protooncogenes and anaplastic lymphoma kinase (ALK), was upregulated.…”
Section: Effects Of Terahertz Waves On Nucleic Acidsmentioning
confidence: 99%
“…These researchers found that terahertz waves promoted the differentiation of mouse pluripotent stem cells after 12 h of radiation by upregulating the expression of peroxisome proliferator-activated receptor gamma, adiponectin, glucose transporter 4 and human adipocyte fatty acids. Zhao et al [58] used a wide-band terahertz source to radiate three different types of cells, epithelial cells, human corneal epithelial cells and human M lymphocytes, under an 800 nm pulse with a repetition rate of 1 kHz, an average power of 1 mW and a peak power of up to 2 mW. Six hours after radiation, the expression of numerous genes, such as protooncogenes and anaplastic lymphoma kinase (ALK), was upregulated.…”
Section: Effects Of Terahertz Waves On Nucleic Acidsmentioning
confidence: 99%
“…Over the past few years, THz technologies have been widely developed due to all kinds of potential applications in imaging, biomedicine, communications, security scanning, and so on. [1][2][3][4][5] The THz emission and the THz detection are two important tasks in THz science. In present, there are several types of THz radiation sources, such as, free electron laser that has the advantages of wide spectrum range, high peak power and average power, and good coherence, but is huge in size and inconvenient to use, electro-optic crystal THz pulse source that the THz electromagnetic pulse is radiated on the crystal surface through the optical rectification effect of nonlinear optics, and THz radiation source based on electronic oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al found that Escherichia coli exposed to 3.1 THz radiation had significant changes in plasmid replication, resulting in increased protein expression 29 . The effect of long‐term (6 h) terahertz irradiation on human cells was investigated by Zhao et al It was found that long‐term terahertz irradiation generated a specific change in gene expression resulting in abnormal chromosome number (aneuploidy) in some daughter cells 30 . Borovkova et al used terahertz radiation (0.12–0.18 THz, 3.2 mW/cm 2 ) to test the cytotoxicity of rat glial cells.…”
Section: Introductionmentioning
confidence: 99%
“…29 The effect of long-term (6 h) terahertz irradiation on human cells was investigated by Zhao et al It was found that long-term terahertz irradiation generated a specific change in gene expression resulting in abnormal chromosome number (aneuploidy) in some daughter cells. 30 Borovkova et al used terahertz radiation (0.12-0.18 THz, 3.2 mW/cm 2 ) to test the cytotoxicity of rat glial cells. It showed that the relative number of apoptotic cells increased 1.5 times after 1 min of terahertz radiation exposure.…”
Section: Introductionmentioning
confidence: 99%